Enhanced coagulation for treating the micropolluted water: Effects of dosages and pH on coagulation performance and residual Al. Issue 6 (29th July 2016) - Hu, Wenchao; Lu, Shaoming; Wang, Yujie
Abstract : The feasibility of using enhanced coagulation which combined polyaluminum chloride (PAC) with diatomite (as coagulant aid and adsorbent) for improving coagulation performance and reducing residual Al was investigated. The effects of dosages (PAC and diatomite) and water pH on coagulation performance and residual Al were mainly discussed. Results demonstrate that compared with PAC alone, coagulation performance was obviously improved by the enhanced coagulation. Meanwhile, the contents of residual total Al (RTAl) and residual total dissolved Al (RTDAl) significantly reduced. PAC and diatomite dosages affected the results of the enhanced coagulation. The best coagulation performance was obtained at PAC dose of 20 mg/L and diatomite dose of 40 mg/L. However, RTAl and RTDAl both achieved the lowest concentrations (0.185 mg/L and 0.06 mg/L, respectively) at PAC 15 mg/L and diatomite 40 mg/L. The water pH also had significant effects on coagulation performance and residual Al. 96.31%, 37.01%, and 51.88% of turbidity, dissolved organic carbon (DOC), and UV254 removals were succeeded, respectively, at pH about 7.99. RTAl and RTDAl achieved the minimum contents (0.133 mg/L and 0.044 mg/L, respectively) at pH 6.95 or so. © 2016 American Institute of Chemical Engineers Environ Prog, 35: 1687–1692, 2016